2003
DOI: 10.1038/nature01640
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3α regulates production of Alzheimer's disease amyloid-β peptides

Abstract: Alzheimer's disease is associated with increased production and aggregation of amyloid-beta (Abeta) peptides. Abeta peptides are derived from the amyloid precursor protein (APP) by sequential proteolysis, catalysed by the aspartyl protease BACE, followed by presenilin-dependent gamma-secretase cleavage. Presenilin interacts with nicastrin, APH-1 and PEN-2 (ref. 6), all of which are required for gamma-secretase function. Presenilins also interact with alpha-catenin, beta-catenin and glycogen synthase kinase-3be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
875
3
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,106 publications
(930 citation statements)
references
References 30 publications
39
875
3
13
Order By: Relevance
“…Inhibition of GSK-3β activity through its phosphorylation can prevent apoptotic cell death and potentially block amyloid toxicity and neurodegenerative disease [10,41,42]. We demonstrate that neuronal protection by Wnt1 may require integration of the GSK-3β pathway that involves phosphorylation and inhibition of GSK-3β activity via Akt1.…”
Section: Discussionmentioning
confidence: 82%
“…Inhibition of GSK-3β activity through its phosphorylation can prevent apoptotic cell death and potentially block amyloid toxicity and neurodegenerative disease [10,41,42]. We demonstrate that neuronal protection by Wnt1 may require integration of the GSK-3β pathway that involves phosphorylation and inhibition of GSK-3β activity via Akt1.…”
Section: Discussionmentioning
confidence: 82%
“…b-Catenin levels are significantly reduced in AD individuals bearing presenilin mutations (Zhang et al, 1998) and active GSK3b accumulates in vivo in AD brains (Pei et al, 1999), where it has a key role in the hyperphosphorylation of the microtubule-associated protein tau (Hanger et al, 1992;Lovestone et al, 1994;Lucas et al, 2001;Sato et al, 2002;Li et al, 2006). Moreover, Wnt signaling may also have an essential role in the processing of the amyloid precursor protein (Mudher et al, 2001;Sun et al, 2002;Phiel et al, 2003), as well as in the neurotoxicity of its derivative the amyloid b-peptide (Ab) (Takashima et al, 1998a;Alvarez et al, 2002;De Ferrari et al, 2003;Alvarez et al, 2004;Caricasole et al, 2004). Remarkably, it has been reported that Ab neurotoxicity induces the expression of Dickkopf 1 (Dkk1) (Caricasole et al, 2004), which may further antagonize Wnt presentation to its complex receptor.…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 99%
“…Anti-amyloid activities include modulation of secretase activities via membrane "fluidity"/protein mobility changes or Akt > GSK regulation of ␥-secretase [25] and induction of anti-amyloidogenic transthyretin [26]. Like fish oil, DHA from algal sources can be safely taken as a supplement at high doses.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%